Critical success factors of contractors in drainage, sewerage and irrigation sector in Abu Dhabi, U.A.E - A.A. Hammouda, Younis (2007)
This study examined the factors that underpin the survival of contructor in drainage, sewage and irrigation (DSI) sector in Abu Dhabi in the wake of the closure of 42 of their counterparts over the last one decade. This study investigated the critical success factor (CSFs) of these companies at the corporate level and ranked these CSFs according to their level of importance at the industry level. Data were collected using postal questionnaire survey and face-ta-face interviews from seven companies out of the ten that are still in operation. The respondents were the General Managers, Project Managers, Finance Managers and Human Resource Managers of the participating companies. At the corporate level, the study found that each company rated the importance of CSFs differently. At the industry level, the statistics show that all six factors that were tested (i.e. expertise, project performance, finance, organisation, managers and employees and relationship with outside parties) are critical for the success of contractors in the DSI sector in Abu Dhabi. Furthermore, within these 6 factors, 31 out of the 37 sub-factors were found to be critical, thus supporting most but not all of past studies. Top management of companies can use the findings as a guide in accumulating the necessary factors to succeed in the DSI sector in Abu Dhabi